FAHLORES FROM PORPHYRY Cu-(Mo) DEPOSITS OF THE URALS - O.Yu. Plotinskaya; E.V. Kovalchuk (Минералогия)
The paper describes chemistry of tetrahedrite-tennantite group minerals from three porphyry deposits of the Urals: Mikheevskoe and Tomino porphyry copper deposits on the South Urals and Talitsa Mo porphyry deposit on the Middle Urals. In the deposits studied tetrahedrite-tennantite group minerals deposited either with late mineral assemblages of the porphyry stage or within late subepithermal veins. They vary in composition from tennantite to tetrahedrite with variable Fe and Zn contents. Contents of Cd, Co, Te, Bi, Ag, Se Te, Bi, Ag, S are usually insignificant. However argentotetrahedrite-(Fe) was described within the latest assemblage at the Mikheevskoe deposit, while tennantite-tetrahedrite-(Cd) was noted overgrowing bornite at the Tomino deposit. Most tetrahedrite group minerals do not establish complicated chemical zoning: they are either homogeneous or comprise a core of intermediate tennantite-tetrahedrite composition and a rim with dominating tetrahedrite end-member. This evidences relatively quiet deposition environment with no dramatic variations of PTx parameters which is rather typical for porphyry systems. Comparison with published data shows the tetrahedrite group minerals studied are similar to those from «transitional» subepithermal mineralization.